174 Ct coronary angiography significantly changes treatment targets versus coronary artery calcium scoring in high-risk dyslipidaemia patients. (6th June 2022) - Graby, John; Sellek, James; Bayly, Graham; Avades, Tony; Capps, Nigel; Shipman, Kate; Mbagaya, Wycliffe; Luvai, Ahai; Khavandi, Ali; Loughborough, Will; Hudson, Benjamin; Downie, Paul; et al.
Abstract : Introduction: Dyslipidaemia accelerates atherosclerosis. Patients with genetic dyslipidaemias, Familial Hypercholesterolaemia (FH) being the most common, are at heightened risk of premature cardiovascular events. However, this risk is heterogeneous within identical genotype diseases, and modifiable with treatment. Coronary imaging identifies subclinical atherosclerosis, personalises risk stratification and treatment targets. Coronary artery calcium scoring (CACS) is first-line for primary prevention. However, calcification is a late-stage process in CAD pathogenesis and the CACS has low specificity in young patients with severe FH. CT coronary angiography (CTCA) may identify non-calcific CAD and high risk plaque (HRP) features unseen with CACS. This study aimed to quantify the impact of CTCA vs traditional CACS on clinical management in real-world asymptomatic Lipid Clinic patients. Methods: A retrospective single-centre review of asymptomatic Lipid Clinic electronic patient records with both CACS and CTCA from May 2019 to December 2020. A vignette was compiled for each patient providing all relevant clinical data. CACS was recorded as Agastston score and CTCA as the Coronary Artery Disease - Reporting and Data System (CAD RADS) grading of anatomical stenosis with a modifier for HRP features.Findings were compiled into an anonymised online survey which Consultant Biochemists from across the UK were invited to complete. Data was revealed in a step-wise fashion to the participating clinician: (i) vignette only, (ii) CACS, and (iii) CAD RADS. Clinicians were asked their lipid target and management after each data-point was unblinded. Background information on CACS and CTCA result interpretation was provided prior to participation. Statistical analysis was performed using SPSS v.21 and significance was defined as two-tailed p<0.05. Results: 45 asymptomatic patients (55±9 years, 49% female) were included. 7 Consultant Biochemists from 6 institutions (4 [67%] tertiary/teaching hospitals and 2 [33%] district general hospitals) participated.CACS and CAD RADS assessment of disease burden is presented in Figure 1, with CTCA re-classifying CAD severity vs CACS in 28/45 (62%) patientsLipid targets were altered significantly more frequently with CTCA vs CACS (19% vs 12%; χ2 57.0, p<0.005), even after CACS result available (Figure 2). The LDL target selected was altered by CACS in 12%, and in a further 19% when CAD RADS result was unblinded, which was statistically significant (χ2 57.0, p<0.005). This finding was consistent across FH and non-FH patients. Increasing CACS and CAD RADS severity were significantly associated with change in lipid target (χ2 54.2, p<0.001; χ2 27, p<0.001), the latter even after a high CACS result was available, as did presence of HRP (χ2 9.3, p=0.002). Conclusion: In high-risk asymptomatic dyslipidaemia, CTCA alters treatment targets beyond CACS by demonstrating higher CAD severity burden and HRP. This may differentiate high risk and very high risk patients in an important population. Conflict of Interest: Nil